A Case of Apparent Lung Adenocarcinoma Size Reduction During Steroid Therapy. Issue 6 (November 2015) - Sato, Yoshinao; Oikado, Katsunori; Tominaga, Junya; Sakurada, Akira; Saito, Ryoko; Takase, Kei
Abstract : Spontaneous regression of lung cancer is a rare phenomenon. We described a case of lung adenocarcinoma size reduction during steroid therapy. In this case, histopathologic findings showed a lung adenocarcinoma surrounded by obstructive pneumonia and inflammatory cell infiltration. Steroid use might have diminished the inflammatory response around the lung cancer, resulting in the apparent shrinkage of the lung cancer. This phenomenon is a potential pitfall in lung cancer diagnosis.